Commuting Behaviors of People with Disabilities and the Implications for Transport Planning and Policy: A Preliminary Study - Fitri, Husnul (Journal of Regional and City Planning, 2024)
This research aimed to obtain an initial understanding of the commuting behaviors of people with disabilities, which has not been widely discussed in the transportation planning literature in Indonesia. Facets studied included frequency of weekly commuting; trip duration to the workplace; trip chaining behavior; usage of public transportation; and utilization of private vehicles. Commuting trips were limited to the home-work-home context, and the research was conducted on adult disabled commuters (aged 17 to 60) in the Jakarta Metropolitan Area (Jabodetabek). A total of 51 commuters with motor and sensory (visual and auditory) disabilities participated in the survey. The results indicate that people with disabilities tend to spend more hours commuting; use public transportation, with the TransJakarta Bus Rapid Transit and paratransit in the form of online motorcycle taxis as the primary modes of transport; and engage in pre-planned trip chaining activities, primarily for visiting family, friends, and clients as well as doing grocery shopping and getting medical treatment. The research findings can serve as valuable resources for developing inclusive transportation policies and planning, such as improving and enhancing access to public transportation for people with disabilities, supporting inclusive training policy in the public transportation field, implementing TOD strategies, and advancing transportation technology to enhance convenience for people with disabilities.